(untitled) (XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2019)
The reprise of the «XY» magazine publication, in the field of an interesting and intelligent publishing project, suitable for its time, that regards the I Libri di XY book series, too, is an important event. In order to quickly regain its prestigious space in the field of scientific publications of the specific disciplinary area, and not only, it is important to wonder why such a long stop – over fifteen years – has took place. Maybe the main reason can be found in the role that the magazine wanted to cover – a place of critical and wide thought, not only regarding architectural representation but also on the usage of pictures in arts and science – for which the building Italian community of graphic representation wasn’t ready, yet. Some of the «XY» were even felt as a kind of provocation, in some ways heretic, as a consequence of a cultural opening that exalted the multidisciplinary push in the unitarity and recomposition of knowledge, doubt and discussion, whereas the main topic looked for at the moment was disciplinary identity, through certainty and orthodoxy. The magazine spread ideas, not only architectural drawings; it stimulated theoretical thinking, non only the improvement and acquisition of practical operative procedures. Maybe for this reason it was the only Italian reality to be somehow part of the debate on themes and objective of the graphic representation scientific–disciplinary area to develop internationally, between the end of the past millennium and the following, especially in congresses and scientific societies, while they were being invested by the infographic revolution that shocked the end of the past century. It’s important to wonder whether, gone by the revolution, there are the conditions to create a place of constant cultural debate, in the field of the rising area of visual image elaboration, not only for architecture but also for science and arts.